2013
DOI: 10.5301/ejo.5000377
|View full text |Cite
|
Sign up to set email alerts
|

Temperament Profile in Patients with Central Serous Chorioretinopathy: A Case-Control Study

Abstract: The patients with CSCR demonstrated less exploratory behaviors, higher risk avoidance, restraint, and low extravagance. They were more quick-tempered, disorganized, and easily frustrated, with a tendency to avoid negative and potentially harmful stimuli, less tolerance to frustration, higher level of insecurity, and higher level of anticipatory anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“… 9 Other risk factors are pregnancy, use of antibiotics, antihistamines, alcohol, smoking, and respiratory diseases. 10 16 Further, Conrad et al 17 showed that patients with CSCR were more stressed as a result of inadequate coping strategies and a higher incidence of physical complaints.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Other risk factors are pregnancy, use of antibiotics, antihistamines, alcohol, smoking, and respiratory diseases. 10 16 Further, Conrad et al 17 showed that patients with CSCR were more stressed as a result of inadequate coping strategies and a higher incidence of physical complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous steroids use has been reported to aggravate subretinal fluid accumulation in CSC patients throughout numerous studies from past to present [13][14][15]. Nonetheless, one of the most important predisposing factors yet to be described and investigated in detail are the psychopathological features such as specific personality traits, psychological stress, and psychiatric illness [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%
“…Harrington and Zeligs suggested that anxiety precipitates autonomic vasomotor instability, which is another pathogenic model of CSC [18]. Thereafter other papers have focused on emotional distress, higher anticipatory anxiety levels, inadequate coping strategies with psychological stress, poor quality of life (QoL) status, and psychiatric disorders [19][20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yanuzzi reported a high prevalance of Type A behavior for the first time with a study as 60 % in the CSC group compared with 40 % in the control group [2]. Piskunowicz et al characterized CSC patients as quick-tempered, disorganized, and easily frustrated, with a tendency to avoid negative and potentially harmful stimuli, less tolerance to frustration, a higher level of insecurity, and a higher level of anticipatory anxiety [3]. Drici et al investigated the reaction of patients with type A and type B behaviors to placebo and found more subjects with a behaviour pattern A (competitive and aggressive) (50 %) described as subjective side effects of the placebo than with type B subjects (17 %) [4].…”
mentioning
confidence: 99%